Analysis of How Local Online News Helped Shape Waste Management Policies in the Aftermath of the COVID-19 Pandemic - Indiahono, Dwiyanto (KnE Social Sciences, 2023)
The purpose of this study was to provide an overview of the role played by local online news in improving policies on waste management in the aftermath of the COVID-19 pandemic. This subject is worth examining since online news, as one of the pillars of democracy, must be able to present its strategic roles on issues of public concern at all levels. This research was conducted using the content analysis method. The study found that Radar Banyumas, a local online news media based in Banyumas Regency, published 28 news articles related to waste issues during the study period, which can be categorized into three major groups: policy articles, social criticism articles, and best practice articles. The study shows that Radar Banyumas is able to play an ideal role in influencing public policy agenda, overseeing policy implementation, providing education to the public, and providing solutions to waste problems. Radar Banyumas has acted as an ideal medium to help shape waste management policies at the regional level. Keywords: waste, local online news media, social criticism, policy recovery